UN NOUVEAU TANYPROCTOIDES PETROVITZ, 1971 D’IRAN (Coleoptera, Melolonthidae) - Montreuil, Olivier; Keith, Denis (Fragmenta entomologica, 2013)
A new species of the genus Tanyproctoides Petrovitz, 1971, T. (Odontiellus) gormicus n. sp., is described from Iran and compared with its most related species. This is the fifth species of this genus.